The Effect of Learning Using Mini Size Balls on Basketball Dribble Skills - Agus Mulyawan (Journal of Physical Education and Sport Science, 2019)
The problem that is the focus of this research is the low availability of dribble balls in basketball games for seventh grade male students of basketball dribbling skills in seventh grade male students. The purpose of the study was: To find out the basketball dribbling skills of students before learning using mini-size balls on male students of class VII and To find out basketball dribbling skills of students after learning using mini-size balls on male students of class VII. The method used in this research is the experimental method. Sampling in this study was taken by probability sampling technique. The population in this study were class VII male students totaling 129 people. The sample set is class VII B (20 students) and VII C (20 students). Based on the results of calculations and data analysis, it can be concluded that: 1) There is no increase in basketball dribbling skills of students before learning using mini-size balls on male students of class VII; 2) There is an increase in basketball dribbling skills of students after learning using mini-size balls on male students of class VII; 3) There is a significant effect of learning to use mini-size balls on basketball dribbling skills in class VII male students.